2012
DOI: 10.1159/000339692
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Amatoxin Poisoning in the State of Texas

Abstract: Ingestion of mushrooms from the genus Amanita can present detrimental consequences to the human body. The mushroom is frequently found in the coastal Pacific Northwest, Pennsylvania, New Jersey, and Ohio. Amanitin, one of the two distinct toxins isolated from the Amanita mushroom, is responsible for the majority of symptoms and signs seen with mushroom poisoning. Clinically, ingestion of these mushrooms can result in a wide range of clinical symptoms including nausea, vomiting, crampy abdominal pain, and diarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…A. phalloides (Death Cap), A. bisporigera, A. rubescens, A. ocreata, A. verna, and Amanita virosa (the last three are referred to as Death Angels and Destroying Angels; however, A. phalloides is also sometimes referred to as Death Angel and A. verna is sometimes referred to as White Death Cap), A. fuliginea, A. subjunquillea, A. exitialis, A. suballiacea, A. tenuifolia, A. hygroscopica as well as some Galerina and Lepiota (e.g., L. brunneoincarnata and L. helveola) species contain amatoxin. As little as 0.1 mg amatoxin/kg body weight may be lethal in adults [36,37,[84][85][86][87][88].…”
Section: Hepatotoxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…A. phalloides (Death Cap), A. bisporigera, A. rubescens, A. ocreata, A. verna, and Amanita virosa (the last three are referred to as Death Angels and Destroying Angels; however, A. phalloides is also sometimes referred to as Death Angel and A. verna is sometimes referred to as White Death Cap), A. fuliginea, A. subjunquillea, A. exitialis, A. suballiacea, A. tenuifolia, A. hygroscopica as well as some Galerina and Lepiota (e.g., L. brunneoincarnata and L. helveola) species contain amatoxin. As little as 0.1 mg amatoxin/kg body weight may be lethal in adults [36,37,[84][85][86][87][88].…”
Section: Hepatotoxinsmentioning
confidence: 99%
“…While the amount of amatoxin varies among species, a single mushroom may contain 5-7 mg of amatoxin and could be fatal if ingested [36,37,[84][85][86][87][88]. Children are particularly sensitive to amatoxin [14,37,[89][90][91][92].…”
Section: The Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…ALT en çok 1227 IU/L, AST de en çok 1378 IU/L olarak ölçülmüş, INR ise en çok 3-3,5 arasında seyretmiştir. Yoğun bakımdaki takipleri sırasından istenen hepatoloji konsültasyonu sonrasında penisilin G tedavisi başlanmış ve tedavi sonrasında hastanın laboratuvar sonuçları hızlıca düzelmiş ve 2 gün sonra servise alınarak taburcu edilmiştir (7). Sunduğumuz olgularda da gastrointestinal şikayetler mevcut olup, ALT ve AST değerleri yükselmiş, INR değerleri her iki olguda da 24. saatte normalin üzerinde ölçülmüştür.…”
Section: Discussionunclassified
“…It is one of the most poisonous known toadstools, being associated with severe symptoms, high morbidity and mortality (85,125). Despite warnings, wild edible and A. phalloides mushrooms are frequently mistaken and every year several cases of intoxications are reported (6,50,120,126,127). Other authors has indicated a potentially significant variation in the amount of amatoxins contained in mushrooms collected at different geographical areas (27).…”
Section: Polymyxin B Prevented α-Amanitin-induced Renal and Hepatic Dmentioning
confidence: 99%